Success breeds success locally: a tale of incubator firms - Eren Inci (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
This paper focuses on the pre-establishment period of start-ups in industrial districts. The industrial architecture is what I call a "rationed agglomeration" in which some entrepreneurs gather around an established firm while other entrepreneurs in the same business stand alone. In a rationed agglomeration, I analyze the eects of relations between established firms, network entrepreneurs, and local financiers on the market prices of loans. I show that such relations improve the match of capital to ideas in the network even though the overall distribution of capital to ideas remains unchanged. This suggests that success breeds success in the networks of established firms. The existence of networks overturns the claim that there are no motives to engage in information gathering in a simple market regime with information asymmetries. In particular, I show that there are market incentives for established firms to decrease the information gap between network entrepreneurs and local financiers.
Keywords: L26; D82; R12; G20; 330; agglomeration; entrepreneur; dispersion; innovation; local financiers; networks; regional economies; project financing; signaling; start-up